IMMUNOHISTOCHEMICAL COMPARATIVE STUDY OF PERIPHERAL, PERI-IMPLANT, AND CENTRAL GIANT CELL LESIONS - PIRES, FABIO RAMOA; DE LIMA MORAIS, THAYNÁ MELO; SOARES, CIRO DANTAS; URIZAR, JOSÉ MANUEL AGUIRRE; NAVARRO, JAVIER ALBERDI; DE ALMEIDA, OSLEI PAES (Oral surgery, oral medicine, oral pathology and oral radiology, 2020)
Central giant cell lesions (CGCL) and peripheral giant cell lesions (PGCL) are reactive lesions of unknown etiopathogenesis and similar histologic features. PGCL affects the gingiva and alveolar mucosa, but some rare cases can be associated with dental implants. Objective: In the present study, we compared the expression of smooth muscle actin, Bcl-2, GLUT-1, CD68, OPG, RANK, Ki67, and CD34 in a series of CGCL and conventional and peri-implant PGCL. Study Design: Clinical data were retrieved from the laboratory records and histologic analysis was performed in hematoxylin and eosin (H&E)-stained sections. Immunohistochemical reactions for detecting the above mentioned antibodies were performed and digitally scored. Results: The digital scores for CD68 and Bcl-2 were higher in conventional PGCL and CGCL than in peri-implant PGCL (P = .033 for CD68 and P <.0001 for Bcl-2). Microvessel density was higher in the conventional PGCL than in CGCL and peri-implant PGCL (P = .002). Conclusions: The current results demonstrated some differences in microvessel density, proliferative activity, and expression of CD68 and Bcl-2 among conventional PGCL, peri-implant PGCL and CGCL. Further studies are encouraged to better understanding of these early findings.